Analysis of Electrical Potential in a Thermoelectric Generator Utilizing Cooking Stove Waste Heat - Pauzi, Gurum Ahmad; Aprilia Habibah; Ali Akbar Raksa Gandi; Yulianti, Yanti; Warsito; Apriyanto, Donni Kis (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2025)
The need for sustainable alternative energy sources has driven increasing interest in waste heat utilization, particularly from domestic and commercial activities such as cooking stoves. This study analyzes the potential for electrical energy generation from waste heat produced by commercial restaurant stoves using a multi-module thermoelectric generator (TEG) system based on Peltier modules (TEC1-12706 and TEG 1848) equipped with a cooling mechanism. The experimental procedure involved characterizing the electrical performance of the modules under a controlled heat source, followed by direct application to an LPG stove with variations in the distance between the heat source and the module to meet specific temperature conditions. The results demonstrate a strong nonlinear relationship between the temperature difference (delta T) and the output voltage, with optimal performance observed within a delta T range of 40 to 65 degrees Celsius. During stove testing, the system generated a maximum output power of 804 milliwatts at a delta T of approximately 53 degrees Celsius. These findings indicate that the utilization of stove waste heat through serially connected TEG modules combined with active thermal management represents a feasible approach for direct current electricity generation in waste heat recovery applications. However, the overall efficiency remains constrained by internal module resistance and thermal contact instability under real operating conditions.